SIKAP SISWA TERHADAP HATE SPEECHS DI SMA NEGERI 1 KERITANG - Annisa Huwaida Firoos; Raja Arlizon; Donal Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Abstract: The purpose of this research is to find out how the general attitude of male and female students towards hate speech and to find out the role of Bk teachers in viewing hate speech. Data collection techniques in this study used questionnaires, interviews. The research subjects were determined using a total sampling technique, namely 124 students of class XI Social Sciences who met the requirements for researchers processing questionnaire data using SPPS 21. The results of the study as a whole were students' attitudes towards hate speech originating from hate speech carried out on social media the students of SMA Negeri 1 Keritang are in the very high category with the proportion of this being seen in the proportion per indicator. It can be seen that based on male and female gender, it turns out that they have a high category.Key Words: Attitudes, Hate Speeches